Aplikasi pemberian pupuk organik dan pemotongan umbi terhadap pertumbuhan dan produksi bawang merah (Allium ascolonicum L.) di lahan kering - Aminah, Iin Siti; Rosmiah, Rosmiah; Palmasari, Berliana; Delfina, Dinda (Universitas Muhammadiyah Mataram, 2022)
Red onion (Allium ascalonicum L.) is a spice plant whose needs as a kitchen spice continue to increase. Some of the obstacles faced in meeting community needs include the availability of inorganic fertilizer needs and seed preparation before planting. From this fact, it is necessary to cultivate through the use of organic fertilizers by cutting bulbs on shallot seeds before planting, so that it is expected to obtain the expected results. The study was conducted from May to July 2021. Field experiments were carried out using the split plot design method, as the main plot. Cutting tubers (P): P0 tubers that were not cut, P1 cutting in parts, P2 cutting in parts and subplots, namely the dose of organic chicken manure (D) D0 control, D1 15 tons/ha, D2 20 tons/ha. Plant variables include plant length (cm), number of leaves (strands). number of tubers per clump (tubers), number of tubers per plot (tubers), fresh weight of tubers per clump (g), fresh weight of tubers per plot (kg). The results showed that by giving a dose of chicken manure 20 tons/ha by cutting onion bulbs, the highest yield was 1.64 kg/plot or equivalent to 4.47 tons/ha